Modeling surface fire rate of spread within a thinned Anatolian black pine stand in Turkey - Kucuk, Omer; Bilgili, Ertugrul; Uzumcu, Rifat (Editorial CSIC, 2018)
Aim of the study: To develop regression models for estimating the rate of surface fire spread in a thinned even-aged black pine stand (Pinus nigra J.F. Arnold subsp. nigra var. caramanica (Loudon) Rehder).Area of the study: The study was carried out within a thinned black pine forest located in the Kastamonu Forest District, northwestern Turkey. The study area is located at 546819, 4577880 UTM.Material and methods: A total of 33 small scale surface fires were ignited under varying weather and fuel conditions. Line ignition was used during the burnings. Surface fuels consisted generally of thinned material (needle+branches).Main results: Within the stand, surface fuel loading ranged from 3.0 to 10.2 kg/m2. Wind speed ranged from 0.3 to 8.4 km/h. Needle moisture content ranged from 8 to 15%. The rate of fire spread ranged from 0.47 to 6.92 m/min. Relationships between the rate of fire spread and fuel and weather conditions were determined through regression analyses.Research highlights: Wind speed was the most important factor on the rate of fire spread and explained 85% of the observed variation in the surface fire rate of spread within a stand.
Keywords: regression models; experimental fire; Forestry; experimental fire; surface fuels; regression models; SD1-669.5; surface fuels; 15. Life on land